Skill Improvement for Public Health Center Staffs in the Management of Toxic and Hazardous Materials - Djuari, Lilik; Dewanti, Linda; Sulistiawati, Sulistiawati; Mahendra, Arya Ivan; Fahruddin, Ahmad Cholifa (Folia Medica Indonesiana, 2022)
Highlight: • There was an increase in the accumulation of B3 waste in health centers during the COVID-19 pandemic. • The knowledge and skills level of health center staff in medical THM waste management before and after medical THM waste management training were determined. • Medical THM waste management training was increasing the knowledge and skills level of health center staff. Abstract: The generation of medical toxic and hazardous material (THM) waste at public health centers tends to increase during the Covid-19 pandemic. Only 6.89% of the health centers have medical waste management practices that meet the standards. Medical waste management practices not in accordance with the procedures can be a source of infection, even though only 56% of health workers have good knowledge and attitudes in solid medical waste management. For this reason, it is necessary to increase the skills of health center staff in managing medical THM waste during the Covid-19 pandemic. The purpose of this study was to determine the level of knowledge and skills of health center staff in medical THM waste management before and after medical THM waste management training. The training participants were 20 health center staffs who filled out a pretest questionnaire to measure their level of knowledge and skills prior to the training. The training materials include THM waste, medical THM waste, medical THM waste management and medical THM Temporary Storage. After the training, a post-test was conducted to measure the knowledge and skills scores of the trainees. The results of this study indicated that there was a significant difference in knowledge before and after training (p < 0.05). The average knowledge score before training was 6.2 (sufficient knowledge) and after training 8.15 (good knowledge). There was a significant difference in skill scores before and after training (p <0.05). The average skill before training was 6.3 (adequate) and after training 8.65 (good). In conclusion, there was an increase in the skills of health center staff in managing medical THM waste during covid-19 pandemic after participating in medical THM waste management training by the Community Service Team, Department of Public Health and Preventive Medicine, Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia.